Organization of area hV5/MT+ in subjects with homonymous visual field defects - Papanikolaou, Amalia; Keliris, Georgios A.; Papageorgiou, T. Dorina; Schiefer, Ulrich; Logothetis, Nikos K.; Smirnakis, Stelios M. (NeuroImage (Orlando, Fla.), 2019)
Damage to the primary visual cortex (V1) leads to a visual field loss (scotoma) in the retinotopically corresponding part of the visual field. Nonetheless, a small amount of residual visual sensitivity persists within the blind field. This residual capacity has been linked to activity observed in the middle temporal area complex (V5/MT+). However, it remains unknown whether the organization of hV5/MT+ changes following early visual cortical lesions. We studied the organization of area hV5/MT+ of five patients with dense homonymous defects in a quadrant of the visual field as a result of partial V1+ or optic radiation lesions. To do so, we developed a new method, which models the boundaries of population receptive fields directly from the BOLD signal of each voxel in the visual cortex. We found responses in hV5/MT+ arising inside the scotoma for all patients and identified two possible sources of activation: 1) responses might originate from partially lesioned parts of area V1 corresponding to the scotoma, and 2) responses can also originate independent of area V1 input suggesting the existence of functional V1-bypassing pathways. Apparently, visually driven activity observed in hV5/MT+ is not sufficient to mediate conscious vision. More surprisingly, visually driven activity in corresponding regions of V1 and early extrastriate areas including hV5/MT+ did not guarantee visual perception in the group of patients with post-geniculate lesions that we examined. This suggests that the fine coordination of visual activity patterns across visual areas may be an important determinant of whether visual perception persists following visual cortical lesions. •We studied hV5/MT+ responses in patients with early visual cortical damage.•We developed a new population receptive field measurement method.•We found responses in hV5/MT+ arising inside the scotoma for all patients.•Responses in hV5/MT+ originate either from V1 or from V1-bypassing pathways.•Activity in either V1 and/or hV5/MT+ is not sufficient to mediate conscious vision.